NASIONALISASI PT INALUM MENURUT UNDANG-UNDANG PENANAMAN MODAL (UNDANG-UNDANG NO. 25 TAHUN 2007) : PRO KONTRA INDONESIA DAN JEPANG - Wuryandari, Utji Sri Wulan (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2016)
Research in the sphere of Foreign Investments would be so remote in Indonesia, this research examines the Japanese joint venture legal entity with Indonesia, PT. Inalum which have a potential asset in supporting the improvement of the people's economy. Furthermore PT Inalum engaged in the aluminum smelting ore in North Sumatera that has a hydroelectric power plant which can generate 600 Megawatts of electricity. In Act number 25 of 2007 on Investment Article 7 declared that the nationalization of foreign investment companies occur with requirements, therefore in this study examines the "Nationalization PT Inalum according to Investment Law in Indonesia." Although this research is done normatively but we conducted interviews with informants of the Japanese in this case Mrs. Haruna Hiroko and delivery guidance interview conducted via email to a resource, Prof. Yuketa Hiroshi of Touin University in Yokohama, Japan. Results of the research noted that the completion of the nationalization of PT Inalum in Indonesia is not resolved by the Foreign Arbitration Board, as the mandate of the Act, but it is done by deliberation. Keywords: Foreign Investments, Indonesia